2019
DOI: 10.3389/fphar.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Reference Genes for Expression Analysis in Chinese Medicinal Herb Huperzia serrata

Abstract: Huperzine A (HupA) is a powerful and selective inhibitor of acetylcholinesterase. It has attracted widespread attention endangering the ultimate plant sources of Lycopodiaceae family. In this study, we used Huperzia serrata, extensively used in Traditional Chinese medicine (TCM), a slow growing vascular plant as the model plant of the Lycopodiaceae family to develop and validate the reference genes. We aim to use gene expression platform to understand the gene expression of different tissues and developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…No single reference gene has been determined that is always expressed stably under any condition (Argyropoulos et al 2006). Accordingly, it is crucial to discover suitable internal control genes with stable expression for the study of specific transcriptional profiles of genes of interest under a certain experimental condition for a certain species (Yang et al 2019). There are many reports on screening for proper reference genes in plants, however, there has been no report regarding reference genes for the study of B. striata.…”
Section: Introductionmentioning
confidence: 99%
“…No single reference gene has been determined that is always expressed stably under any condition (Argyropoulos et al 2006). Accordingly, it is crucial to discover suitable internal control genes with stable expression for the study of specific transcriptional profiles of genes of interest under a certain experimental condition for a certain species (Yang et al 2019). There are many reports on screening for proper reference genes in plants, however, there has been no report regarding reference genes for the study of B. striata.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that GAPDH was often applied as stable RG in different tissues or under various experimental conditions (Chen et al, 2017 ; Zhuang et al, 2015 ). Especially for H. serrata , GAPDH also was proved as stable RG by Yang et al ( 2019 ). TBP was also identified as stable RG for H. serrata by Yang et al ( 2019 ).…”
Section: Discussionmentioning
confidence: 94%
“…Especially for H. serrata , GAPDH also was proved as stable RG by Yang et al ( 2019 ). TBP was also identified as stable RG for H. serrata by Yang et al ( 2019 ). Unfortunately, TBP gene could not be amplified in our materials.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations